Kewenangan Pawang Glee terhadap Penyelesaian Sengketa Antarwarga dalam Pemanfaatan Hutan di Aceh Berdasarkan Prinsip Utilitarianisme - Hasnitaria Hasnitaria; Nouvan Moulia; Fazzan Fazzan (Pencerah, 2022)
This research aimed to find out the authority of Pawang glee on the conflict completion among people in forest utilization in Aceh, also to find out the suitability of conflict completion among people in forest utilization in Aceh with utilization principle. The technique of conflict completion obtained in Article 1 Paragraph (10) The Law Number 30 Year of 1999 About The Alternative of Conflict Completion explains that conflict can be solved outside the court through the methods of consultation, negosiation, mediation, consiliation, and expert assessment. This research was a normative juridicial research, the approach used in this research was the law regulation approach and historical approach. The result of this research showed that Pawang glee authority on conflict completion among people in forest utilization in Aceh has been suitable with the utilization principle of natural resources which centers on the prosperity manifestation for all people of Indonesia. The existence of institution and authority of Pawang glee in managing forest utilization through traditional law has continuously been strengthened with the presence of Aceh Qanun Number 10 Year of 2008 About Traditional Institution. The weakness which must be improved from the conflict completion this far mediated and solved by Pawang glee was not documented and published well yet until the work result of Pawang glee institution could not be accessed widely by the community.